PENGARUH VARIABEL MAKROEKONOMI TERHADAP PERTUMBUHAN KREDIT BANK UMUM DI INDONESIA - Sinta Yulyanti; Poppy Camenia Jamil; Haugesti Diana (UIR Press, 2023)
The aim of this research is to determine the effect of variables Macroeconomics on Credit Growth in Commercial Banks in Indonesia. The analysis technique used in this research is panel data regression analysis which is used to statistically test the hypothesis model, as well as the extent to which the proposed model is consistent with the sample data. The results of the T-test study show that GDP growth and interest rates (BI Rate) have a positive and insignificant effect on credit growth in commercial banks in Indonesia. Meanwhile, the inflation variable and the Rupiah/USD exchange rate have a negative and insignificant effect on credit growth in commercial banks in Indonesia.